Impacts of Birds vs. Invertebrate Predators on Rocky Intertidal Community Structure - Bruce A. Menge (Ecology and Evolution)
ABSTRACT Most studies of species interactions in rocky intertidal communities focus on invertebrate predators and herbivores interacting with sessile invertebrates and macrophytes. However, shorebirds are usually a conspicuous presence on rocky shores and eat sessile and mobile invertebrate prey, often including invertebrate predators and herbivores. Inspired by classic studies of strong bird predation effects in rocky intertidal habitats in Washington state (USA) and South Africa, I tested the effects of bird and invertebrate (sea stars, whelks) predation at multiple sites, wave exposures, and zones on the central Oregon coast from spring 1996 to fall 1997. To gain insight into the effects of birds relative to the effects of invertebrate predators, I used a crossed design, with bird exclusions (present and absent) and invertebrate predator removal (present and reduced). Compared to Washington state and South Africa, birds had little effect on the abundance of sessile or mobile prey in wave‐exposed mid, wave‐exposed low, and wave‐protected mid zones at 2–4 sites. I suggest that differences between Oregon results and those in Washington and South Africa were driven by differences in bird abundance associated with whether the study site had resident colonies of shorebirds (primarily gulls, crows, and oystercatchers). That is, offshore islands often have resident breeding colonies such as in the Washington and South African studies, while sites in this study were all on the mainland where gulls were mostly transient visitors, while resident oystercatchers were usually limited to one or two pairs per site. Comparison with other marine and terrestrial experimental tests suggests that top‐down effects of birds often vary in strength, and thus, future investigations should seek to understand the factors that underlie this variation.